Activation of the motor protein upon attachment: Anchors weigh in on cytoplasmic dynein regulation. (3rd May 2016) - Ananthanarayanan, Vaishnavi
Abstract : Cytoplasmic dynein is the major minus‐end‐directed motor protein in eukaryotes, and has functions ranging from organelle and vesicle transport to spindle positioning and orientation. The mode of regulation of dynein in the cell remains elusive, but a tantalising possibility is that dynein is maintained in an inhibited, non‐motile state until bound to cargo. In vivo, stable attachment of dynein to the cell membrane via anchor proteins enables dynein to produce force by pulling on microtubules and serves to organise the nuclear material. Anchor proteins of dynein assume diverse structures and functions and differ in their interaction with the membrane. In yeast, the anchor protein has come to the fore as one of the key mediators of dynein activity. In other systems, much is yet to be discovered about the anchors, but future work in this area will prove invaluable in understanding dynein regulation in the cell. Abstract : Cytoplasmic dynein is the primary minus‐end‐directed motor protein in the cell. Dynein that is bound to the cortex via anchor proteins is required for nuclear organisation. Activation of dynein upon attachment to anchor proteins is emerging as one of the mechanisms of dynein regulation in vivo.